Konflik Peran Ganda Dan Manajemen Stres Kerja Karyawan Wanita Di PT Krakatau Steel (Persero) Tbk - Widiyanto, Afif; Sanusi, Fauji (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2021)
The dual role experienced by female employees can create stress which, if it happens continuously, will interfere with employee productivity and performance in the company. This study aims to determine the effect of work family conflict on employee performance through job stress management as an intervening variable and social support as a moderating variable. The research was conducted on women employees at PT Krakatau Steel (Persero) Tbk with a total sample of 100 people. The data analysis in this study used the Structural Equation Modeling approach which was processed by SmartPLS program. From the research conducted, it is concluded that 1) work family conflict has a positive and significant effect on employee performance, 2) work family conflict has a positive and significant effect on work stress management, 3) job stress management has a positive and significant effect on employee performance, 4) social support does not moderate the relationship of work family conflict to job stress management, 5) social support weakens the relationship of work family conflict to employee performance.